A new genus and species of freshwater Hadziidae, Fluviadulzura spinicauda gen. nov., sp. nov. from rivers in Victoria, Australia (Amphipoda) - Myers, Alan A.; Lowry, James K.; Billingham, Zac (Zootaxa, 2017)
A new species of fresh-water amphipod, Fluviadulzura spinicauda gen. nov. sp. nov. is described from rivers in Victoria, Australia. The taxon is fully described and figured.